Comparative adversaria of Gandhi and Marx: self-clarification through thinking in diaries and letters. - Hutnyk, John (Inter-Asia Cultural Studies, 2023)
We can now see in the public sphere almost everything written by Karl Marx and Mohandas Karamchand Gandhi. Both are widely read, and both have had major impacts on how many people, if not all in some way, understand political activity. Both were prolific writers, but their ideas would exceed the forms in which they were expressed. Access to even their most intimate writings—diary, drafts, notebooks, personal letters—perhaps allows us to better see, in a retrospective way, their thinking unfold. Looking at private correspondence, notebooks and diaries of famous political figures reveal writing as a tool of self-clarification, providing insight into the labour required as a prelude to formal publication. Seeking out how public texts were rehearsed and assembled in more intimate forms for the ears of others also raises questions about who gets to write and read, and of course, what is retained and what is excluded by publication. Comparing Marx's notebooks and drafts with Capital or Gandhi's daily diary with its published versions might mean asking different self-clarifying questions, in our different contexts of distraction. And of Marx and Gandhi, might we ask if it is still possible for someone politically engaged to write all the time? An emphasis on "adversaria" may itself be a privileged diversion, available only to those who will be measured in turn.